The Small RNA ErsA of Pseudomonas aeruginosa Contributes to Biofilm Development and Motility through Post-transcriptional Modulation of AmrZ - Falcone, Marilena; Ferrara, Silvia; Rossi, Elio; Johansen, Helle K.; Molin, Søren; Bertoni, Giovanni (Frontiers in Microbiology, 2018)
The small RNA ErsA of Pseudomonas aeruginosa was previously suggested to be involved in biofilm formation via negative post-transcriptional regulation of the algC gene that encodes the virulence-associated enzyme AlgC, which provides sugar precursors for the synthesis of several polysaccharides. In this study, we show that a knock-out ersA mutant strain form a flat and uniform biofilm, not characterized by mushroom - multicellular structures typical of mature biofilm. Conversely, the knock-out mutant strain showed enhanced swarming and twitching motilities. To assess the influence of ErsA on the P. aeruginosa transcriptome, we performed RNA-seq experiments comparing the knock-out mutant with the wild-type. More than 160 genes were found differentially expressed in the knock-out mutant. Parts of these genes, important for biofilm formation and motility regulation, are known to belong also to the AmrZ transcriptional regulator regulon. Here, we show that ErsA binds in vitro and positively regulates amrZ mRNA at post-transcriptional level in vivo suggesting an interesting contribution of the ErsA-amrZ mRNA interaction in biofilm development at several regulatory levels.